Attitudes of subjects at risk and their relatives towards genetic counselling in Huntington's chorea. Issue 3 (June 1983) - Tyler, A; Harper, P S
Abstract : Ninety-two patients suffering from Huntington's chorea (HC) and their spouses, and 91 subjects with an affected parent and their spouses, living in three counties of industrial South Wales, have been studied regarding their knowledge of their inheritance of the disorder. Particular attention was paid to its influence on their attitudes towards child-bearing, telling their children of the risks, and predictive tests. Only 12% of the patients were known to have received professional advice before completing their families, in contrast to 68% of the sample at risk. It is estimated that 82% of the patients and 60% of the subjects at risk had, or might have, restricted their family size had they known in time. The majority found genetic counselling helpful, but did not necessarily wish to alter their child-bearing plans in consequence. It was clear that information provided by the family alone was usually inadequate and that this applied to the present generation at risk as well as to previous generations. It was concluded that the burden of telling children the risks is too great for most parents and that professional help is needed. The long term impact of genetic counselling on the incidence of the disease is impossible to assess without continued monitoring, but preliminary results are encouraging. Attitudes towards a predictive test reflected much conflict: although 56% overall wished to take one, only 40% of those who were parents wished to know if they were at risk of passing the gene on to their children. Few subjects reported severe social stress on learning of their genetic risks, but about one in four reported experiencing significant anxiety.